(untitled) (Revista Contexto & Educação, 2022)
The article discusses the process of choosing a federal technical high school by the students from low-income backgrounds. Based on studies on the choice of school institution and access to higher education of low-income people, we conducted in-depth interviews with ten students, belonging to the lower classes, from the Federal Institute of Education, Science and Technology of São Paulo (IFSP). As a result, all students interviewed can be considered “good students” and there was a noticeable participation of teachers in the process of choosing the school, by providing information and encouraging these student’s admission to the IFSP. It has revealed that the choice of the federal institution by the popular strata occurred through a socially constructed process, especially at the school level, during the students’ schooling. Keywords: Choose. School. Low-income backgrounds.